STRATEGI INDONESIA DALAM MENINGKATKAN KEAMANAN MARITIM MELALUI CORAL TRIANGLE INITIATIVE ON CORAL REEFS, FISHERIES AND FOOD SECURITY (CTI-CFF) - Wahyuni, Fajrianti; Saeri, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
CTI-CFF is a form of multilateral cooperation that Indonesia utilizes to strengthen maritime security through conservation and sustainable management approaches. This study aims to analyze Indonesia's strategy in improving maritime security through the implementation of CTI-CFF programs. This study employs a descriptive qualitative approach with an institutional neoliberalism theoretical framework. The primary focus is on the role of institutions in creating cooperation mechanisms that foster trust, transparency, and compliance in addressing transnational maritime challenges. The results of this study show that through three main programs, Indonesia has successfully utilized CTI-CFF not only for conservation purposes but also as a strategic instrument in addressing non-traditional maritime security threats. Indonesia's active involvement in this institution strengthens its diplomatic position and reflects its consistency in maintaining collective regional stability. Keywords: CTI-CFF, Indonesia, Maritime Security, Multilateral Cooperation